2016
DOI: 10.1121/1.4948571
|View full text |Cite
|
Sign up to set email alerts
|

Pile driving playback sounds and temporary threshold shift in harbor porpoises (Phocoena phocoena): Effect of exposure duration

Abstract: High intensity underwater sounds may cause temporary hearing threshold shifts (TTSs) in harbor porpoises, the magnitude of which may depend on the exposure duration. After exposure to playbacks of pile driving sounds, TTSs in two porpoises were quantified at 4 and 8 kHz with a psychophysical technique. At 8 kHz, the pile driving sounds caused the highest TTS. Pile driving sounds had the following: pulse duration 124 ms, rate 2760 strikes/h, inter-pulse interval 1.3 s, duty cycle ∼9.5%, average received single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In the present study, no significant difference was observed in the mean TTS after exposure of the study animal to 10 successive double airgun shots and 20 successive double airgun shots (Table IV). Kastelein et al (2016b) observed only a very small increase in TTS (the ratio of TTS increase to the associated increase in SELcum was $ 0.5 dB/dB) between 30 min and 6 h exposures of harbor porpoises to impulsive pile driving playback sounds (1.3 s inter-pulse intervals, duty cycle $9.5%). The same phenomenon was observed in other TTS studies in which harbor porpoises were exposed to intermittent fatiguing sounds and continuous sounds (Kastelein et al, 2014a;Kastelein et al, 2016a).…”
Section: Effect Of Number Of Airgun Exposures On Ttsmentioning
confidence: 86%
See 3 more Smart Citations
“…In the present study, no significant difference was observed in the mean TTS after exposure of the study animal to 10 successive double airgun shots and 20 successive double airgun shots (Table IV). Kastelein et al (2016b) observed only a very small increase in TTS (the ratio of TTS increase to the associated increase in SELcum was $ 0.5 dB/dB) between 30 min and 6 h exposures of harbor porpoises to impulsive pile driving playback sounds (1.3 s inter-pulse intervals, duty cycle $9.5%). The same phenomenon was observed in other TTS studies in which harbor porpoises were exposed to intermittent fatiguing sounds and continuous sounds (Kastelein et al, 2014a;Kastelein et al, 2016a).…”
Section: Effect Of Number Of Airgun Exposures On Ttsmentioning
confidence: 86%
“…First, a recording of a single pile driving sound (an impulsive sound that was used as a substitute for airgun sounds during the training phase) was played back via an underwater transducer (Lubell LL1424HP; see Fig. 1 for position) up to the level of a SELss of 145 dB re 1 lPa 2 s (see Kastelein et al, 2016b).…”
Section: Sound Exposure Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…However, published records of VHF-weighted SELs of seal bombs are lacking. Among the stimuli studied for harbor porpoises, pile driving and seismic airguns are most similar to seal bombs due to their high-intensity, broadband impulses with strong lowfrequency components (Hermannsen et al, 2015;Kastelein et al, 2016). Thresholds for TTS and PTS in "Very High-Frequency" odontocetes including harbor porpoises, have been based on studies of these stimuli (Southall et al, 2019).…”
Section: Noise-induced Threshold Shiftmentioning
confidence: 99%